Impact and Strategy of PT. Dirgantara Indonesia (DI) to Get Out of the Crisis During the Covid 19 Pandemic - Tommy Rahadian Setiaji; Muhammad Syaroni Rofii; Achmad Sanusi (Konfrontasi: Jurnal Kultural, Ekonomi dan Perubahan Sosial, 2022)
During the Covid-19 pandemic, it strikes all over the world. One of them is in the field of aviation, especially flights in Indonesia. The innovation process for public transportation companies that produce transportation services to the public who use transportation services (users), then in principle there are four functions of transportation service products, namely safe, orderly and regular, comfortable, and economical. The research methodology used is qualitative. The existence of the strategic defense industry of PT. Dirgantara Indonesia (DI) is a manifestation of the desire of the Indonesian people to use domestically produced defense equipment aimed at supporting the defense system.